Aerial view of Barbados - (:unkn) unknown (My University, 2018)
Aerial view of Barbados showing entrance to the Careenage. The Careenage is located in the heart of Barbados’ capital city Bridgetown. The name was given as this was the place where ships were careened onto a side to be repaired, scrubbed and painted. The area was once filled with activity from merchants who would dock their ships and unload all kinds of merchandise which would then be stored in the nearby warehouses.
Landscape, black & White, 4 x 6 in.
Keywords: Boats; Aerial view; Ships; Careenage